2019
DOI: 10.1007/s10841-019-00135-z
|View full text |Cite
|
Sign up to set email alerts
|

Trends and indicators for quantifying moth abundance and occupancy in Scotland

Abstract: Moths form an important part of Scotland's biodiversity and an up-to-date assessment of their status is needed given their value as a diverse and species-rich taxon, with various ecosystem roles, and the known decline of moths within Britain. We use long-term citizen-science data to produce species-level trends and multi-species indicators for moths in Scotland, to assess population (abundance) and distribution (occupancy) changes. Abundance trends for moths in Scotland are produced using Rothamsted Insect Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 60 publications
2
46
0
1
Order By: Relevance
“…Reductions in total insect biomass in multidecadal studies are similarly being reported from different parts of the globe: a 33% reduction in the abundance of butterflies was observed over 21 years in extensive monitoring in Ohio, United States (Wepprich, Adrion, Ries, Wiedmann, & Haddad, 2019); abundance of 176 moth species decreased by 20% from 1975 to 2014 in Rothamsted insect survey samples in Scotland (Dennis et al, 2019); total flying insect biomass decreased by more than 70% across 63 study F I G U R E 1 With almost 1 million described species, insects eclipse all other forms of animal life on Earth, not only in sheer numbers, diversity, and biomass but also in their importance to functioning ecosystems. A few representatives of that great insect diversity are shown here, as follows: Top row, left to right: monarch butterfly (Danaus plexippus), violet dropwing dragonfly, (Trithemis annulata), luna moth (Actias luna), polished lady beetle (Cycloneda munda), snowberry clearwing moth (Hemaris diffinis), jagged ambush bug (Phymata sp.)…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Reductions in total insect biomass in multidecadal studies are similarly being reported from different parts of the globe: a 33% reduction in the abundance of butterflies was observed over 21 years in extensive monitoring in Ohio, United States (Wepprich, Adrion, Ries, Wiedmann, & Haddad, 2019); abundance of 176 moth species decreased by 20% from 1975 to 2014 in Rothamsted insect survey samples in Scotland (Dennis et al, 2019); total flying insect biomass decreased by more than 70% across 63 study F I G U R E 1 With almost 1 million described species, insects eclipse all other forms of animal life on Earth, not only in sheer numbers, diversity, and biomass but also in their importance to functioning ecosystems. A few representatives of that great insect diversity are shown here, as follows: Top row, left to right: monarch butterfly (Danaus plexippus), violet dropwing dragonfly, (Trithemis annulata), luna moth (Actias luna), polished lady beetle (Cycloneda munda), snowberry clearwing moth (Hemaris diffinis), jagged ambush bug (Phymata sp.)…”
Section: Introductionsupporting
confidence: 59%
“…Reductions in total insect biomass in multidecadal studies are similarly being reported from different parts of the globe: a 33% reduction in the abundance of butterflies was observed over 21 years in extensive monitoring in Ohio, United States (Wepprich, Adrion, Ries, Wiedmann, & Haddad, 2019); abundance of 176 moth species decreased by 20% from 1975 to 2014 in Rothamsted insect survey samples in Scotland (Dennis et al, 2019); total flying insect biomass decreased by more than 70% across 63 study locations over 27 years in Germany (Hallmann et al, 2017) and a more than 10-fold reduction in arthropod biomass was observed from 1976 to 2012 in a resampling study from the Puerto Rican rainforest (Lister & Garcia, 2018). Although there has been some criticism of specific studies (Thomas, Jones, & Hartley, 2019), the overall trend is clear and the broad geographic reach is perhaps the most dire feature of the current crisis, as assessments from all continents except Antarctica reveal declines.…”
Section: Introductionsupporting
confidence: 59%
“…To accurately capture the underlying trend in the rate of change requires simultaneously and repeatedly sampling populations with standardised devices (New, 1998). Since 1964, the Rothamsted Insect Survey has been at the forefront of the insect declines research, exploiting the longest standardised terrestrial insect time series in the world, reporting on population change in aphids, moths, ladybirds, wasps and general insect biomasses (Taylor, 1974;Conrad et al, 2002Conrad et al, 2007;Woiwod & Gould, 2008;Shortall et al, 2009;Fox et al, 2013;Comont et al, 2014;Bell et al, 2015;Lester et al, 2017;Martay et al, 2017;Coulthard et al, 2019;Dennis et al, 2019;Fox et al, 2019;Macgregor et al, 2019). In this article, we build on this extensive knowledge and present an analysis of the likely scale of moth and aphid population linear and non-linear trends over Great Britain and, how rates of change vary according to habitat and spatial scale.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasise that simply because analysis of occurrence data result in occupancy trend outputs that meet the precision threshold, this is not proof that the outputs are true: if the model is mis-specified or the data are biased then the outputs can be precise but wrong (see discussion by Dennis et al (2019) and Kamp et al (2016)). When considering the accuracy of the trend outputs, it is important to ask whether the trends can be considered representative.…”
Section: Discussionmentioning
confidence: 99%